TEACHING HEARING IMPAIRED LEARNERS ENGLISH IN ZAMBIA : The embeddedness of colonial ideas in current educational policies and curriculum in primary schools - Hamoonga, Linda (My University, 2021)
Zambia is a former British colony hence has adopted the English language as the major language of instruction in schools. Regardless of the latter, Zambia has seen several language of instruction policy changes from 1925 to 2013. Lower primary schools have experienced the most changes because they are viewed as the foundation for successful acquisition of literacy skills. Similarly to the colonial era these changes have not improved literacy rates among learners. Several researchers have alluded to the Eurocentric curriculum introduced by missionaries in the early 1900‘s in Zambia to be responsible for the low literacy rates and disconnect between learners and their social-cultural environment. Therefore, the purpose of this thesis is to investigate the embeddedness of colonial policies in current Zambian educational policies and curriculum. The thesis uses the postcolonial and social-cultural theories to analyze the colonial and postcolonial educational policies with special focus on teaching hearing impaired learners. The Postcolonial theory strength lies in the analysis of culture as a tool used by colonizers to subdue nations through educational practices that negated the learners‘ social-cultural environment. The social-cultural theory asserts that the learners‘ community (culture) is important for successful literacy acquisition, thus helps situate the postcolonial theory in classroom practice. Thus the main research objective of this thesis is to investigate the similarities between colonial language of instruction educational policies and the current Zambian policies and curriculum. The paradigm adopted in critical theory was applied to investigate the colonial cultural imperialism and the Vertical Case Study approach helped structure the macro and micro levels of policy analysis. Interviews (teacher interviews) and document analysis were the main data collection methods used while thematic analysis was used to analyze the data. The analysis disclosed that colonial educational policies were influenced by the biological theories attached to the intellectual capabilities of ‗black‘ people, which were deemed lower than all the other races. These views were mostly blamed on the social cultural practices which warranted changing through adapting the education system. Educational policies based on adaptive education meant maintaining natives‘ social position and ways of life. Thus native languages were largely used within the education system until the fourth grade which was the last grade of formal schooling for the majority of native learners. Consequently, when Zambia gained independence it decided to adopt the education system offered to European children, an educational system which was not based on indigenous ways of knowing. English became the official language of instruction. Similarly to the period of colonial educational policies, the learner is still alienated from the local community. The education system has resulted in different identities among natives; the native identity and hybridity; a merge of the European culture and the native culture. Hybridity, from the colonial era to date is enhanced through the provision of substandard education through unqualified teachers, inadequate material provision and Eurocentric curriculum. All the latter compromise literacy acquisition and impairs the ability of learners to become a productive member of society and enjoy their rights. Finally, the analysis illustrates the evolving nature of educational policies. Physical and human spaces and identities may change as a result of social, political, geophysical and economic factors, but concepts which define these identities and spaces remain the same with an evolution on how they are interpreted. Therefore, extensive research needs to be conducted to fully understand the role literacy skills are to play in local communities. With such vital research, responsive and effective policies that improve literacy skills will be developed.
Keywords: post colonialism, social-cultural theory, colonialism, special education, curriculum and policies, teaching methods, hearing impaired learners